Restless pilgrim : Andrew Jenson's quest for Latter-day Saint history - Neilson, Reid L., 1972-; Marianno, Scott D. (University of Illinois Press, 2022)
"When Danish immigrant and Latter-day Saint convert Andrew Jenson left his homeland as a teenager for the American West in 1866, he envisioned a better life in a land of seemingly endless economic and spiritual possibilities. Instead, the Latter-day Saint kingdom in the West, then squarely outside accepted notions of American respectability, brought new challenges. Trapped in a cycle of intermittent wage work, Jenson reimagined himself as a journalist and advocate for Latter-day Saint Scandinavians in Utah Territory. He quickly evolved into a self-made historian for The Church of Jesus Christ of Latter-day Saints. For the next fifty years until his death in 1941, Jenson documented the church's transition away from its insular nineteenth-century past toward a more modern future. This book chronicles the life and career of historian Andrew Jenson, a prolific writer and longtime employee of the Historian's Office, the church's main archive. Jenson reformed institutional record keeping, expanded the church's primitive archive, and traveled over one million miles to gather Latter-day Saint history around the globe. This book charts a different course for the field of Latter-day Saint biography by telling the story of a life outside the church's hierarchy. Additionally, this book uses Jenson's life to narrate a larger history of the Historian's Office while offering a fresh perspective on a remarkable era of global growth and change for the church"--